Resilience and Sustainability of Muslim Entrepreneurs of Gen Z In Era 5.0: A Conceptual Approach - Mayvita, Prihatini Ade; Rifani, Ahmad (RSF Conference Series: Business, Management and Social Sciences, 2024)
This study investigates how digital innovation and green marketing contribute to the resilience and sustainability of Muslim Generation Z entrepreneurship. Gen Z, known for its strong affinity for technology, utilizes digital platforms such as social media and e-commerce to develop businesses with relatively low capital, making it an ideal environment for entrepreneurial growth. For Muslim Gen Z entrepreneurs, integrating Islamic values like honesty, social responsibility, and business ethics into their ventures is essential for business practices. The study aims to explore the impact of digital entrepreneurship and green marketing on the resilience of Muslim Gen Z entrepreneurs and identify the factors influencing their sustainability. The research employs a conceptual approach, analyzing secondary data and existing literature on digital entrepreneurship, green marketing, and Islamic business ethics. Findings indicate that leveraging digital technology enhances the ability of Muslim Gen Z entrepreneurs to adapt to market changes, increase competitiveness, and operate sustainably. Green marketing, in particular, aligns with Islamic principles of environmental responsibility, attracting environmentally conscious consumers and building stronger brand loyalty. This study highlights how these entrepreneurs can integrate ethical practices with innovative strategies to build resilient and sustainable businesses in the digital era. The research underscores the need for further empirical studies to examine the practical application of Islamic values and digital innovation across various regions and how these factors interact with local entrepreneurial ecosystems.